HERV-K and LINE-1 DNA Methylation and Reexpression in Urothelial Carcinoma - Kreimer, Ulrike; Schulz, Wolfgang A.; Koch, Annemarie; Niegisch, Günter; Goering, Wolfgang (Frontiers in Oncology, 2013)
Changes in DNA methylation frequently accompany cancer development. One prominent change is an apparently genome-wide decrease in methylcytosine that is often ascribed to DNA hypomethylation at retroelements comprising nearly half the genome. DNA hypomethylation may allow reactivation of retroelements, enabling retrotransposition, and causing gene expression disturbances favoring tumor development. However, neither the extent of hypomethylation nor of retroelement reactivation are precisely known. We therefore assessed DNA methylation and expression of three major classes of retroelements (LINE-1, HERV-K, and AluY) in human urinary bladder cancer tissues and cell lines by pyrosequencing and quantitative reverse transcription–polymerase chain reaction, respectively. We found substantial global LINE-1 DNA hypomethylation in bladder cancer going along with a shift toward full-length LINE-1 expression. Thus, pronounced differences in LINE-1 expression were observed, which may be promoted, among others, by LINE-1 hypomethylation. Significant DNA hypomethylation was found at the HERV-K_22q11.23 proviral long terminal repeat (LTR) in bladder cancer tissues but without reactivation of its expression. DNA methylation of HERVK17, essentially absent from normal urothelial cells, was elevated in cell lines from invasive bladder cancers. Accordingly, the faint expression of HERVK17 in normal urothelial cells disappeared in such cancer cell lines. Of 16 additional HERV-Ks, expression of 7 could be detected in the bladder, albeit generally at low levels. Unlike in prostate cancers, none of these showed significant expression changes in bladder cancer. In contrast, expression of the AluYb8 but not of the AluYa5 family was significantly increased in bladder cancer tissues. Collectively, our findings demonstrate a remarkable specificity of changes in expression and DNA methylation of retroelements in bladder cancer with a significantly different pattern from that in prostate cancer.